Indonesian Human Resources Readiness in term of Facing the ASEAN Economic Community - Fathin, Cinintya Audori; Perdana, Arika Bagus; Kartikasari, Ayu; Sulistyastuti, Dyah Ratih (Jurnal Ilmu Sosial dan Ilmu Politik, 2014)
This article explains about the dilemma which will be faced by Indonesia when the the Mutual Recognition Arrangement (MRA) is implemented in the ASEAN Economic Community (AEC) by the end of 2015. The data which will be used to describe the existing condition of the human resources competitiveness in Indonesia in this article is the secondary data, such as Human Development Index (HDI); World Knowledge Competitiveness Index (WKCI); Global Knowledge Competitiveness Index (GKCI); Global Talent Competitiveness Index (GTCI); Global Innovation Index (GII); and The Networked Readiness Index. Where upon, these indices will be used as the guidance to compare the human resources quality in Indonesia with Singapore, Malaysia, Thailand, and the other ASEAN countries.Based on the data analysis, these indices show that Indonesian human resources are still far left behind in terms of competition with the other three ASEAN countries. It is feared that the weak competitiveness of human resources in Indonesia may cause the influx of the foreign skilled workers in more significant numberas a consequence of the implementation of MRA.This paper has been presented on ICONAS Forum at 2nd October 2014 by the first writer, and later it has been developed by the other 3 writers.